Evaluation of the International League Against Epilepsy 1981, 1989 and 2017 classifications of seizure semiology and aetiology in a population-based cohort of children and adults with epilepsy - Egesa, IJ; Newton, CR; Kariuki, SM (Wiley, 2021)
Objective: The International League Against Epilepsy (ILAE) has revised the classification of epilepsies and seizures on several occasions since the original classification published in 1964. It is unclear if these changes have impacted the characterization of epilepsy, including the clinical validity of seizure semiology or epilepsy outcomes in resource-poor areas. We aim to address this important knowledge gap.